PENGARUH SIKAP DAN MINAT BELAJAR TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PAKET C - Putri, Youlinda Loviyani; Rifai, Achmad (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
This research aims to describe and analyze attitudes, learning interests, learning motivation, attitudes towards learning motivation, the influence of interest in learning to learn motivation, and influence attitude and interest to learn motivation. This research uses a quantitative approach with a descriptive method. Data collection techniques using research questionnaires and documentation of the ex-post facto research type, and its analytical techniques are double linear regression techniques. The population in this study is a student of education equality package C SKB Jepara. Sampling in this study uses probability proportionate random sampling. The results showed the level of attitude, interest, and motivation to learn students Package C SKB Jepara is said to be